(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Takra (buttermilk) is included under the Pathya kalpna (dietetic preparations) because of its use as both medicine and a dietary regime. Takra is called as Amruta for the patients suffering from the diseases caused by Mandagni (low digestive power). Detail description about Takra is mentioned in all classical texts of Ayurveda. It plays important role in diseases namely Arsha (hemorrhoids), Grahani (irritable bowel syndrome), Udara (ascities) and Agni vikruti. The properties of Takra (buttermilk) according to Ayurveda are mentioned as Laghu (light), Anushna (not hot in potency), Grahi (absorbant), Dipana (appetizing), Madhur vipak (sweet taste after digestion) and Tridhoshaghna. Because of this unique combination Takra can be included in daily diet for all type of Prakruti (constitution of person). In this study Takra along with its various types, their properties, and methods of preparation and health benefits has been studied critically on the basis of principles and practices of Ayurveda. This study will bring about novel understanding of nutritional and therapeutic uses and newer preparations of buttermilk.